Relationship Between the Personal Characteristics and the Attitudes of Adequate and Balanced Nutrition of the Students at the Faculty of Sports Sciences - Dalbudak, Ibrahim; Yasar, Oznur; Afyon, Yakup Akif; Celikbilek, Sinan; Mulazimoglu, Olcay (Progress in Nutrition, 2021)
Study Objectives: This study aimed to examine the relationship between personality traits and adequate and balanced nutrition attitudes of students studying in different departments in the Faculty of Sport Sciences at Ege University and actively doing sports in different sports branches. Methods: In this study, the “Adequate and Balanced Nutrition Scale” was used to evaluate the nutritional habits of the students and the “Ten-item Personality Scale” was used to measure the personality traits. “Personal Information Form” was used to evaluate the data regarding the demographic characteristics of university students. SPSS 23.0 program was used in the analysis of the data. Totally, 186 students voluntarily participated in the study. Results: Considering the relationship between the ten-item personality scale and its subscales, and the attitude scale and its subscales about adequate and balanced nutrition, important results stand out. As individuals’ knowledge, anxiety and interest in adequate and balanced nutrition increase, their general personality scale scores also increase. In addition, as individuals’ extraversion, neuroticism, conscientiousness and agreeableness levels increase, their attitudes towards adequate and balanced nutrition also increase (p